Debt and Seniority: An Analysis of the Role of Hard Claims in Constraining Management - Hart, Oliver; Moore, John (American Economic Review, 1995)
We argue that long-term debt has a role in controlling management's ability to finance future investments. Companies with high (widely held) debt will find it hard to raise capital, since new security-holders will have low priority relative to existing creditors; conversely for companies with low debt. We show that there is an optimal debt–equity ratio and mix of senior and junior debt if management undertakes unprofitable as well as profitable investments. We derive conditions under which equity and a single class of senior long-term debt work as well as more complex contracts for controlling investment behavior.